What is Vitamin D Deficiency Dangerous and How to Diagnose it (The Peerian Journal, 2022)
For most people, vitamin D is linked to the bones—given in the form of fish oil to children to prevent rickets, and TV commercials recommend it to the elderly to protect them from osteoporosis.